1995
DOI: 10.1016/0092-8674(95)90126-4
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin synthase 1 gene disruption in mice reduces arachidonic acid-induced inflammation and indomethacin-induced gastric ulceration

Abstract: Cyclooxygenases 1 and 2 (COX-1 and COX-2) are key enzymes in prostaglandin biosynthesis and the target enzymes for the widely used nonsteroidal anti-inflammatory drugs. To study the physiological roles of the individual isoforms, we have disrupted the mouse Ptgs1 gene encoding COX-1. Homozygous Ptgs1 mutant mice survive well, have no gastric pathology, and show less indomethacin-induced gastric ulceration than wild-type mice, even though their gastric prostaglandin E2 levels are about 1% of wild type. The homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
604
4
16

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,064 publications
(656 citation statements)
references
References 58 publications
30
604
4
16
Order By: Relevance
“…Although LT appear to be the major mediators of AA-induced acute inflammation, it has been demonstrated that prostanoids produced via the COX pathways also play a role in this model (23,(32)(33)(34)(35)(36). Treatment of wild-type mice with the COX inhibitor INDO allowed us to examine the contribution of prostanoids to AA-induced cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although LT appear to be the major mediators of AA-induced acute inflammation, it has been demonstrated that prostanoids produced via the COX pathways also play a role in this model (23,(32)(33)(34)(35)(36). Treatment of wild-type mice with the COX inhibitor INDO allowed us to examine the contribution of prostanoids to AA-induced cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Male COX-1 -/-, COX-1 +/+ , COX-2 -/-, COX-2 +/-, and COX-2 +/+ mice maintained on a C57Bl/6-129/Ola background for over 35 generations [35,41] were received at our animal facility at 6 weeks of age from a private NIEHS colony maintained by Taconic Farms (Germantown, NY) separately from their commercially available colony. In order to prevent the inclusion of strain or genetic background confounders between COX deficient and wild type mice, all of the mice used in this study were derived from a maintenance colony of COX-1 +/-or COX-2 +/-males and females, as previously described [35,41,64]. Specifically, all mice used in this study were progeny derived from heterozygous by heterozygous matings and therefore all contained the same strain and genetic background.…”
Section: Animal Housingmentioning
confidence: 99%
“…However, studies have indicated that this image is more complex, and both constitutively expressed Cox2 and inducible Cox1 genes have been described somewhat depending on tissue (Breder et al 1995;Harris et al 2001). They also seem to be differentially regulated, and have shown to have different function in knock-out mice, whereas COX1 seems to have housekeeping function while COX-2, accounts for the elevated production of prostaglandins (Dinchuk et al 1995;Langenbach et al 1995;Morham et al 1995). In teleosts there are additional copies of cox2, probably due to genome duplication.…”
Section: Introductionmentioning
confidence: 99%